2002
DOI: 10.1364/ol.27.000222
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Bragg grating–based self-referencing technique for wavelength-multiplexed intensity sensors

Abstract: An amplitude-phase-conversion self-referencing technique for intensity-modulated photonic sensors that uses two different-wavelength fiber Bragg gratings is presented. With this technique, the system response has been demonstrated to be almost unafffected by network power variations as high as 90% of the total power launched by the source. We prove the multiplexing capability of this type of self-referenced fiber sensor by wavelength-division multiplexing two of them in a star network. A tunable fused biconica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 6 publications
0
30
0
1
Order By: Relevance
“…Bus and star reflective topologies using FBG have been reported [24][25], employing optical amplification in order to compensate insertion losses of optical couplers; nevertheless, the noise associated to amplification is a limiting aspect. Partial optimizations of power budget using WDM devices at the reception stage have been demonstrated in self-referencing intensity networks [16], but the use of couplers leads to lossy distribution of lightwave channels. A scalable self-referencing sensor network with low insertion losses implemented in Coarse Wavelength Division Multiplexing (CWDM) technology is reported.…”
Section: Multiplexing Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bus and star reflective topologies using FBG have been reported [24][25], employing optical amplification in order to compensate insertion losses of optical couplers; nevertheless, the noise associated to amplification is a limiting aspect. Partial optimizations of power budget using WDM devices at the reception stage have been demonstrated in self-referencing intensity networks [16], but the use of couplers leads to lossy distribution of lightwave channels. A scalable self-referencing sensor network with low insertion losses implemented in Coarse Wavelength Division Multiplexing (CWDM) technology is reported.…”
Section: Multiplexing Techniquesmentioning
confidence: 99%
“…So it is very important to be able to conjugate self-referencing and multiplexing [15][16]. This is one of the main reasons for migration to single-mode fiber (SMF) configurations in self-referenced intensity based sensors networks.…”
Section: Introductionmentioning
confidence: 99%
“…FBG-based self-referencing configurations providing insensitivity to external power fluctuations, non-correlated to the sensor intensity modulation, have also been reported in reflective operation employing in the sensing points all-optical delay line filters [13], as well as Michelson and ring resonator configurations [14], [15]. Recently, we have reported a compact electro-optical design which avoids the need for fiber delay coils, thus achieving compact sensor heads, arbitrary modulation frequency and electronically reconfigurable operation in a single point [16].…”
mentioning
confidence: 99%
“…It is shown that the proposed multiplexing approach optimizes the power budget. The self-referenced measurement parameter is based on the optical configuration detailed in [13], but the Z-Transform technique is used for describing the new system with a doubled sensitivity, obtained by subtracting the output phase signals at two different modulation frequencies.…”
mentioning
confidence: 99%
“…In the experiment, strain measurement with a maximum sensitivity of −0.34 V/ has been achieved. Intensity-modulated fiber-optic sensors have attracted significant interest due to their many advantages including simplicity and potential low cost [1,2]. A large number of parameters can be measured by these sensors with the use of inexpensive light sources and simple detection schemes while still benefiting from the intrinsic advantages of photonic sensors.…”
mentioning
confidence: 99%